2015
DOI: 10.1371/journal.pone.0139985
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptor Protein Myd88 Is a Key Signaling Molecule in the Pathogenesis of Irinotecan-Induced Intestinal Mucositis

Abstract: Intestinal mucositis is a common side effect of irinotecan-based anticancer regimens. Mucositis causes cell damage, bacterial/endotoxin translocation and production of cytokines including IL–1 and IL–18. These molecules and toll-like receptors (TLRs) activate a common signaling pathway that involves the Myeloid Differentiation adaptor protein, MyD88, whose role in intestinal mucositis is unknown. Then, we evaluated the involvement of TLRs and MyD88 in the pathogenesis of irinotecan-induced intestinal mucositis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 46 publications
4
45
0
Order By: Relevance
“…The CPT-11-induced intestinal damage is indicated in the current work by shortened villi, loss of crypts architecture, and intense inflammatory cell infiltrate, in accordance with previous studies described in the literature [9, 10, 27, 28]. The participation of neutrophils and macrophages in the pathogenesis of CPT-11-induced intestinal mucositis had been reported [9, 10].…”
Section: Resultssupporting
confidence: 89%
“…The CPT-11-induced intestinal damage is indicated in the current work by shortened villi, loss of crypts architecture, and intense inflammatory cell infiltrate, in accordance with previous studies described in the literature [9, 10, 27, 28]. The participation of neutrophils and macrophages in the pathogenesis of CPT-11-induced intestinal mucositis had been reported [9, 10].…”
Section: Resultssupporting
confidence: 89%
“…Furthermore, TNFα and IL‐1β induce MMP‐1, MMP‐2 and MMP‐3 activation, which is thought to contribute to development of gut toxicity through inflammatory pathways, altered extracellular matrix composition, adhesion molecules and tight junction disruption. Toll‐like receptor (TLR)4‐dependent mechanisms have also been linked to the development of gut toxicity, with increases in its expression seen following chemotherapy as well as improvements in symptomatic parameters seen following genetic manipulation of its downstream signaling molecules ( e.g., MyD88, MD‐2) . This aspect of CIGT has significant implications for BBB maintenance, as it is becoming increasingly clear that TLR4‐dependent signaling pathways are critical for tight junction integrity …”
Section: Chemotherapy‐induced Cytokine Production Blood Brain Barriementioning
confidence: 99%
“…Toll-like receptor (TLR)4-dependent mechanisms have also been linked to the development of gut toxicity, with increases in its expression seen following chemotherapy 81 as well as improvements in symptomatic parameters seen following genetic manipulation of its downstream signaling molecules (e.g., MyD88, MD-2). 82,83 This aspect of CIGT has significant implications for BBB maintenance, as it is becoming increasingly clear that TLR4-dependent signaling pathways are critical for tight junction integrity. 84 TLR4-mediated barrier modulation has been shown in both endothelial and epithelial models.…”
Section: Vegf Vegf-a Disrupts Claudin-5 and Occludin Expression In Cnmentioning
confidence: 99%
“…These overlapping steps are thought to be largely driven by the activation of NFκB, subsequently promoting key pro-inflammatory cytokines. Furthermore, apoptosis, pathogenic bacteria, inflammation, matrix metalloproteinases (MMPs), loss of mucosal barrier integrity and toll like receptors (TLRs) have also been reported to play an important role in GIM (21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Pathobiology Of Gimmentioning
confidence: 99%
“…TLRs initiate the innate immune response and the production of proinflammatory mediators including IL-1β, nitric oxide and IL-18, whose role in intestinal GIM is well known (32)(33)(34). Recently, TLR/MyD88/NF-κB pathway has been implicated in the mechanisms of damage involved in chemotherapy-related GIM (27). It has also been reported that TLR-2 acts as a central regulator of xenobiotic defense and targeting TLR2 may represent a novel therapeutic approach in chemotherapy-induced GIM (26).…”
Section: Pathobiology Of Gimmentioning
confidence: 99%